Comparison of Palm Oil Mill Effluent Electrocoagulation by Using Fe-Fe and Al-Al Electrodes: Box-Behnken Design - Darmadi Darmadi; Mirna Rahmah Lubis; Hizir Hizir; Aula Chairunnisak; Bastian Arifin (Department of Chemical Engineering, Universitas Gadjah Mada, 2018)
This present research aims to compare the COD removal of palm oil mill effluent (POME) by electrocoagulation using iron and aluminum electrodes. Response surface method coupled Box-Behnken design is applicable to investigate the effect of various process parameters (voltage, operating time and electrolyte concentration) and optimum condition. The optimum condition by using iron electrode is in 43 minutes, 20 volts and 0.06 M NaCl with the COD removal of 95.045%. By using electrode aluminum, optimum condition is 40.35 minutes, 19 volts and 0.1 M NaCl with the COD removal of 89.941%. Energy consumption of iron electrode and aluminum electrode are 0.189 and 0.209 kWh/mg decomposed COD with energy costs of Rp. 255 and Rp. 282/mg decomposed COD. This indicates that energy and cost consumption of electrocoagulation by using Al electrode are higher than those by using iron electrode. Based on the investigation during research, iron electrode is better for reducing COD while the aluminum is better in removing color in POME.